Two species of the genus Anchistrocheles (Bairdioidea: Ostracoda: Crustacea) from Japan and their developmental characteristics for adaptation to interstitial environments - Ito, Misumi; Tsukagoshi, Akira (Zootaxa, 2022)
A new species and an already known species of the genus Anchistrocheles Brady & Norman, 1889 from the Pacific coast of Japan, are described in detail using scanning electron microscopy of the carapaces and soft-part anatomy of the appendages. The new species, Anchistrocheles hayatotanakai sp. nov., is only the second to be described in the genus Anchistrocheles from Japan, and this study is also the first to describe the appendages of A. yamaguchii Yajima, 1987, previously only known as a fossil from Pleistocene strata of the Atsumi Formation in central Japan. The two species are considered to be closely related because they share many common characters in their appendages, but they are distinguishable from each other based on the male and female copulatory organs, furcal chaetotaxy, brush-shaped organs, number of lateral pore systems, and outlines of the carapaces in dorsal view. Ontogenetic changes of carapace sizes were compared between three interstitial species (Anchistrocheles hayatotanakai sp. nov., A. yamaguchii, and Neonesidea sp. I) and an epifaunal species (N. sp. S). The reduction in carapace width was found to be the primary reason for the reduction in the cross-sectional area and is probably related to the adaptation to interstitial environments. The brush-shaped organs located between the 6th pair of limbs are also shown. This study is the first to report the anatomically precise position of these organs.